Paulo Freire, um tesouro do Brasil: entrevista com Professor Dr. Carlos Alberto Torres / Paulo Freire, a treasure of Brazil: interview with Professor Dr. Carlos Alberto Torres - Dalsotto, Mariana Parise Brandalise (CONJECTURA: Filosofia e Educação, 2020)